Tomás Predicador: el auténtico y desconocido. El legado homilético del Aquinate - Fernández Ruiz, Juan Ignacio (2023)
Fil: Fernández Ruiz, Juan Ignacio. Universidad del Norte Santo Tomás de Aquino; Argentina